FEATURES OF DONATING CULTURAL HERITAGE OBJECTS - Choriev Murod Shokirjonovich (Scholar Express Journals, 2021)
The article analyzes methods of increasing the efficiency of using cultural heritage objects. The practice of the modern use of immovable cultural monuments, foreign experience in preserving these objects, economic instruments to support and stimulate investors and private owners of historical monuments are studied. Criteria are described for determining a possible use of a historical and cultural monument. Based on the studies, the most promising direction is highlighted in adapting cultural heritage sites for modern use, ways to solve the problems identified in Russia are proposed to stimulate and support investors and private owners of historical monuments
Keywords: Effective use; cultural heritage sites; economic incentives; legislation